Analysis of Rural-Based Pre-Service Teachers Spatial-Visualisation Skills in Problem Solving in Vector Calculus Using MATLAB - Amevor, Godfred; Bayaga, Anass; Bosse, Michael J. (International Journal of Emerging Technologies in Learning (iJET), 2021)
In science, technology, engineering and mathematics (STEM) for instance, interdisciplinary studies have noted positive correlation between spatial-visualization (SV skills) and mathematical problem solving. The majority of these studies sharing a link between SV skills and problem solving were contextualized in urban settings and only a few in rural settings. This investigation analyses how rural-based pre-service teachers apply their SV skills in problem-solving in a South African university, in the context of vector calculus. One hundred rural-based pre-service teachers in a second year vector calculus class at University of Zululand (UNIZULU) were randomly selected into control and experimental groups. MATLAB was used as a dynamic visual tool to analyse how research participants applied their SV skills. A mixed method approach was employed in data collection (quantitative and qualitative). Our findings revealed that the rural-based pre-service teachers’ SV skills correlate with their problem-solving skills in vector calculus.